The dynamics of unemployment and imprisonment in England and Wales, 1946–1985 - Sabol, William J. (Journal of quantitative criminology, 1989)
This paper explores the dynamic relationship between unemployment and prison admissions in the English criminal justice system. First, by adopting econometric procedures designed to test between alternative forms of dynamic equilibria, it finds that there has been a steady-state growth rate in prison admissions and that unemployment growth has played an important role in determining that equilibrium. Second, by developing a behavioral model of judicial expectations, it argues that judges have used their expectations as heuristic devices for simplifying sentencing decisions and that the unanticipated changes in unemployment have played a key role in determining changes in sentencing patterns. Due to individualized sentencing practices characteristic of English judges, unemployment plays a much larger role in determining prison sentences than warranted under Anglo-American legal traditions.